Momordica charantia extracts ameliorate insulin resistance by regulating the expression of SOCS-3 and JNK in type 2 diabetes mellitus rats. (1st January 2017) - Ma, Chunyu; Yu, Hongyu; Xiao, Ying; Wang, Huijiao
Abstract: Context: Momordica charantia L. (Cucurbitaceae) has long been widely used as a traditional remedy for diabetes mellitus in some countries. However, detailed antidiabetic mechanisms are largely unknown. Objectives: This study clarified the ameliorating effects of M. charantia ethanol extracts (MCE) on the insulin resistance in type 2 diabetes mellitus (T2DM) rats. Materials and methods: T2DM rat model was established by high-fat diet and streptozotocin (STZ) injection. Diabetic rats were randomized into five groups: the model control group ( n = 8) (common diet), the high-fat diet metformin (50 mg/kg/d), and the three-dose MCE (100, 200, and 400 mg/kg/d) groups ( n = 8 each). After 8 weeks, the fasting serum glucose, insulin, TNF-α, and IL-6 were measured, and the relevant factors of glucose and insulin were monitored by glycogen dyeing, RT-PCR, and western blot, respectively. Results: The 8-week treatment of 400 mg/kg MCE significantly lowered body weight (330.1 versus 365.9 g), serum glucose (7.41 versus 16.63 mmol/L), insulin (12.06 versus 15.89 mIU/L), TNF-α (52.72 versus 81.83 ng/L), and IL-6 (104.81 versus 135.74 ng/L) in comparison with those of the diabetic control group ( p < 0.05). It was the same for skeletal muscle glucose transporter 4 (GLUT-4) protein, and glycogen level, suppressor of cytokine signaling-3 (SOCS-3), c-Jun N-terminal kinase (JNK), and Akt expression at both protein and mRNA levels in liver ( p < 0.05). Conclusions: MCE can ameliorate insulin resistance in T2DM rats. This effect may be related to the regulation of mRNA and protein levels of SOCS-3 and JNK.